2021
DOI: 10.1097/cm9.0000000000001797
|View full text |Cite
|
Sign up to set email alerts
|

Selective elimination of host cells harboring replication-competent human immunodeficiency virus reservoirs: a promising therapeutic strategy for HIV cure

Abstract: Many seminal advances have been made in human immunodeficiency virus (HIV)/AIDS research over the past four decades. Treatment strategies, such as gene therapy and immunotherapy, are yielding promising results to effectively control HIV infection. Despite this, a cure for HIV/AIDS is not envisioned in the near future. A recently published academic study has raised awareness regarding a promising alternative therapeutic option for HIV/AIDS, referred to as “selective elimination of host cells capable of producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that latently infected CD4+ T-cells (untreated) display two cell clusters (Cluster 1 and Cluster 2) (63). That is important, as these 2 distinct clusters remain despite treatment with (i) SAHA, a less efficient latency reversing agent (LRA) as shown in the literature (64) or (ii) TCR stimulation (65), which works as a potent LRA. HIV transcript levels were consistently higher in cluster 2 than in cluster 1.…”
Section: Identification Of the Inducible Latent Cell And Potential La...mentioning
confidence: 91%
See 1 more Smart Citation
“…It has been demonstrated that latently infected CD4+ T-cells (untreated) display two cell clusters (Cluster 1 and Cluster 2) (63). That is important, as these 2 distinct clusters remain despite treatment with (i) SAHA, a less efficient latency reversing agent (LRA) as shown in the literature (64) or (ii) TCR stimulation (65), which works as a potent LRA. HIV transcript levels were consistently higher in cluster 2 than in cluster 1.…”
Section: Identification Of the Inducible Latent Cell And Potential La...mentioning
confidence: 91%
“…Before 2018, researchers using single-cell approaches were oriented to the investigation of cellular heterogeneity of the latent reservoir (45,70), and the assessment of cellular response heterogeneity to latency reversal agents (LRAs) (71). This is understandable, as latent reservoirs represent the greatest challenge to HIV eradication (72), and the application of LRAs to reverse latency is one of the strategies that has been explored to treat patients (65). For example, Baxter et al (45), found that latent reservoirs (CD4 + T-cells) from HIV-untreated individuals were predominantly central/transitional memory (Tcm/tm, CD27 + CD45RA -) and Tem (CD27 -CD45RA -) when stimulated with bryostatin [an antineoplastic drug used in clinical cancer trials (73), and also used as an LRA (65)], or not.…”
Section: Characterization Of Hiv-1 Reservoir Diversitymentioning
confidence: 99%
“…“Shock and Kill” aims to reverse HIV latency and increase viral gene expression [Figure 2 A], followed by clearance of infected cells via immune-mediated killing by NK cells, CTLs and bNAbs. [ 57 ] However, “Shock and Kill” has been challenging to achieve. The localization of reactivated CD4 + T cells in protected sites, insufficient expression of HIV Ags by reactivated CD4 + T cells, low levels and impaired function of HIV-specific CD8 + T cells, and presence of CTL escape mutants might affect the effectiveness of “Shock and Kill” strategies.…”
Section: Immune Interventions For Hiv Curementioning
confidence: 99%
“…Despite extensive global research and study (1)(2)(3), a cure for HIV infection has, thus far, proven elusive. Recently, our research group has proposed novel potential therapeutic options for HIV infection (4,5) which, we believe, could inspire future clinical trials into curative therapeutic options for HIV. Our first proposition concerns the promotion of P-selectin glycoprotein ligand 1 (PSGL-1), an important receptor from innate immunity, which (i) induces the production of membrane defective virions that are unable to attach to or infect new target cells, and (ii) blocks the HIV reverse transcription process.…”
Section: Introductionmentioning
confidence: 99%